Modulation of proprioceptive integration in the motor cortex shapes human motor learning - Rosenkranz, Karin; Rothwell, John C. (The journal of neuroscience, 2012)
Sensory and motor systems interact closely during movement performance. Furthermore, proprioceptive feedback from ongoing movements provides an important input for successful learning of a new motor skill. Here, we show in humans that attention to proprioceptive input during a purely sensory task can influence subsequent learning of a novel motor task. We applied low-amplitude vibration to the abductor pollicis brevis (APB) muscle of eight healthy volunteers for 15 min while they discriminated either a small change in vibration frequency or the presence of a simultaneous weak cutaneous stimulus. Before and after the sensory attention tasks, we evaluated the following in separate experiments: (1) sensorimotor interaction in the motor cortex by testing the efficacy of proprioceptive input to reduce GABAAergic intracortical inhibition using paired-pulse transcranial magnetic stimulation, and (2) how well the same subjects learned a ballistic thumb abduction task using the APB muscle. Performance of the vibration discrimination task increased the interaction of proprioceptive input with motor cortex excitability in the APB muscle, whereas performance in the cutaneous discrimination task had the opposite effect. There was a significant correlation between the integration of proprioceptive input in the motor cortex and the motor learning gain: increasing the integration of proprioceptive input from the APB increased the rate of motor learning and reduced performance variability, while decreasing proprioceptive integration had opposite effects. These findings suggest that the sensory attention tasks transiently change how proprioceptive input is integrated into the motor cortex and that these sensory changes drive subsequent learning behavior in the human motor cortex.
Gesehen am 23.04.2018